Supporting data for the paper "Langevin dynamics for a heavy particle immersed within a flow of light particles" - Erban, R; Van Gorder, R A (University of Oxford, 2024)
The attached files contain the supporting data for the paper: "Langevin dynamics for a heavy particle immersed within a flow of light particles" by Radek Erban and Robert A. Van Gorder